A259 ELEVATED BIOCHEMICAL LIVER TESTS WITHIN 1-YEAR TRANSPLANT PREDICTS RECURRENT PSC. (1st March 2018) - Wasilenko, S; Lytvyak, E; Montano-Loza, A J; Mason, A L
Abstract: Background: Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease affecting bile ducts leading to cirrhosis and end-stage liver disease. Liver transplant is the only effective treatment however 6–59% of those transplanted develop recurrent PSC (rPSC). Many risk factors for recurrence have been proposed yet only the presence of ulcerative colitis has been validated in multiple studies. We hypothesized patients who develop rPSC have elevated liver tests within the first year following transplant, as previously observed with recurrent hepatitis C and recurrent autoimmune hepatitis. Aims: To determine if elevated liver tests within 1 year of transplant predicts rPSC. Methods: PSC patients who underwent liver transplant at the University of Alberta Hospital from 1991 to 2015 were included. Recurrent PSC was defined by cholangiography and/or histological findings. Recurrence free survival and graft loss was compared between patients with and without rPSC. Liver tests including alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and bilirubin were assessed at 3, 6, 9, and 12 months after liver transplant. Abnormal liver tests were defined as values above the ULN for ALT, AST and bilirubin or 1.5XULN for ALP. Results: One hundred and thirty-one patients were included. Mean transplant age was 43 years with 98 (75%) males and rPSC occurred in 40/131 (30%) patients. Mean recurrence time was 70 months (4 to 172 months) with rPSC rates of 4% and 20%, at 1 and 5 years, respectively. Median survival time was similar between rPSC and non-rPSC (132 ± 11 vs 175 ± 13 months, P=0.28). Mean time to graft loss was lower in those with rPSC (109 ± 12 vs 180 ± 13 months, P=0.003). Recurrent PSC patients with AST and ALT≥ULN at 12 months had disease recurrence occur earlier than those with normal AST and ALT (19 ± 17 vs 78 ± 50 months, P=0.001) and rPSC developed sooner in patients with ALP≥1.5XULN and ALT≥ULN at 6, 9, and 12 months inclusive (13 ± 4 vs 66 ± 51months, P=0.001). Multiple liver test abnormalities were identified that predict the development of rPSC (see table). Conclusions: Post-transplant abnormal hepatocellular and cholestatic biochemical liver tests within the 1 st year or transplant predicts rPSC. Funding Agencies: None